Binary logistic regression on cafeteria satisfaction services - Che Him, Norziha; Yusof, Yusliandy; Mohamad Aris, Nur Syazwani Aqilah (2020)
This study investigates student’s satisfaction level towards cafeteria services in Universiti Tun Hussein Onn Malaysia (UTHM) locat-ed in southeast Malaysia. A structured self-administered questionnaire survey has been conducted with 360 respondents by using stratified ran-dom sampling. This study adopted the Chi-Square test, Likelihood Ratio test and Binary Logistic Regression. The comparison result shows that students more satisfied to the Campus Cafeteria compared to the College Cafeteria. A significance test for the logistic coefficient by using the Likelihood Ratio test with predictors Food Quality, Staff Skills, Waiting Time and Gender show strong significant predictors that influenced stu-dent’s satisfaction towards cafeteria services. Hosmer-Lemeshow test revealed the greater p-value of Model 1 (0.418) compared to Model 2 (0.261). Therefore, Model 1 has been chosen as the best model with Food Quality, Staff Skills, Waiting Time and Gender were significant factors in influencing the student’s satisfaction towards the cafeteria.